PERENCANAAN PAJAK PADA PT ‘X’ DALAM UPAYA MEMINIMALISIR PAJAK PENGHASILAN BADAN YANG HARUS DI BAYAR (STUDI KASUS PADA PT ‘X’) - Landy, Novia (Jurnal Mahasiswa Perpajakan, 2015)
This research is done on basically different interests in tax payments between taxpayers and the government. For taxpayers, paying taxes are one of the burden of profit because it will reduce the amount received .While for the government , the payment of income tax will be used to a country development. So that taxpayers will try to the best possible in order to minimize taxes. There are many ways the company do in reducing the number of taxes starting from the legal and illegal. The most famous of illegal ways are make financial reports more than one , which will be used to internal company , for determining the amount of tax owed, and to banking transaction. Tax planning is one of way of legal minimize taxes owed .The principle of tax planning is to harness the cracks of the law that profitable. Because any legislation proved that every rules could not include all desired. The data which showed by the researcher tell that, the income tax owed by ‘X’ Company could be minimized with various ways. If ‘X’ Company use tax planning based on the recommendation of the researcher, then ‘X’ Company can minimize 8,27 % of the income tax. Keyowords: Tax planning, company tax income, employee tax income, commercial financial report, fiscal financial  report.